PENGARUH MANAJEMEN WAKTU DAN MOTIVASI TERHADAP PROKRASTINASI MAHASISWA MANAJEMEN UPNVJT - Wicaksono, Muhammad Vicky; Kustini, Kustini (POLITEKNIK LP3I JAKARTA, 2026)
Procrastination in finishing final tasks is a big problem that might make students' study time longer. This tendency was observed among students in the Management Study Program at UPN Veteran East Java, class of 2021, where 16.20% had not commenced their thesis within the designated timeframe. This study seeks to examine the impact of time management and motivation on academic procrastination. This study utilized a quantitative methodology including a sample of 75 students selected from the cohort of 2021 who had not yet finalized their thesis. We used SmartPLS 4.0 software to help us analyze the data. The study's conclusion suggests that a student's proficiency in time management and elevated motivation correlates with a diminished propensity for academic procrastination in thesis completion.